Should product-specific advertisement be regulated in pharmaceutical markets? - Junichiro Ishida; Tsuyoshi Takahara (Osaka University, Institute of Social and Economic Research (ISER), 2022)
This paper examines the optimal content regulation of DTCA by comparing two forms of DTCA-product-specific and category-specific-and identifies a key tradeoff which underlies this policy debate. Our analysis suggests that the optimal form of DTCA depends crucially on the cost effectiveness of DTCA and the market-size distortion induced by DTCA. When the cost of advertisement is high, there often exists a Pareto-improving policy choice: category-specific DTCA is preferred when the marketsize distortion is more severe while produce DTCA is preferred when it is less so. As the cost decreases, however, a conflict emerges between pharmaceutical firms and patients: firms are worse off under product-specific DTCA while patients are better off. We also find that the physician's reluctance to persuade misinformed patients can actually alleviate the market-size distortion and hence be welfare-enhancing.
Keywords: M37; I11; I18; 330; category-specific DTCA; product-specific DTCA; advertisement regulation; prescriptiondecision; pharmaceutical market